Indole-3-carboxyaldehyde does not reverse the intestinal effects of fiber-free diet in mice - Smits, Mark M.; Dreyer, Serafina I. L.; Hunt, Jenna E.; Drzazga, Anna K.; Modvig, Ida M.; Holst, Jens J.; Kissow, Hannelouise (Frontiers in Endocrinology, 2024)
Objective: Fiber-free diet impairs intestinal and colonic health in mice, in parallel with a reduction in glucagon like peptide-1 (GLP-1) levels. Endogenous GLP-1 is important for intestinal growth and maintenance of the intestinal integrity. We aimed to investigate whether fiber-free diet reduces luminal content of metabolites which, upon supplementation, could increase GLP-1 secretion and restore the adverse effects of fiber-free diet. Methods: Untargeted metabolomics (LC-MS) was performed on colonic content of mice fed a fiberfree diet, identifying a metabolite of particular interest: indole-3-carboxyaldehyde (I3A). We exposed cultured GLUTag cells to I3A, and measured cumulative GLP-1 secretion. Isolated colon perfusions were performed in male C57BL/6JRj mice and Wistar rats. I3A was administered luminally or vascularly, and GLP-1 was measured in portal vein effluent. Finally, female C57BL/6JRJ mice were fed chow or fiber-free diet, with I3A or vehicle by oral gavage. After 10 days, plasma GLP-1 (ELISA) and intestinal permeability (FITC-dextran) were measured, animals were sacrificed and organs removed for histology. Results: Mice fed a fiber-free diet had significantly lower I3A in their colonic content compared to a control diet (7883±3375 AU, p=0.04). GLP-1 secretion from GLUTag cells was unchanged after five minutes of exposure to I3A. However, GLP-1 levels increased after 120 minutes of exposure to 1 mM (60% increase, p=0.016) and 5 mM (89% increase, p=0.0025) I3A. In contrast, 48 h exposure to 1 mM decreased GLP-1 secretion (51% decrease, p<0.001) and viability. In isolated perfused mouse and rat colon, I3A applied into the luminal or vascular side did not affect GLP-1 secretion. Mice fed a fiberfree diet tended to weigh less compared to chow fed mice; and the small intestine and colon were significantly smaller. No differences were seen in crypt depth, villus length, mucosal area, and intestinal permeability. Supplementing I3A did not affect body weight, morphology or plasma GLP-1 levels. Conclusions: Fiber-free diet lowered colonic content of I3A in mice. I3A stimulates GLP-1 secretion in vitro, but not in animal studies. Moreover, it has no evident beneficial effect on intestinal health when administered in vivo.